Barriers to Knowing and Being Known: Constructions of (In)competence in Research - Woodfield, Casey; Freedman, Justin (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
In this paper, we examine the barriers to, and possibilities of, recognizing individuals labelled intellectually disabled as producers and contributors to knowledge about their experiences. Through engaging perspectives within the fields of philosophy of education and disability studies, we examine contrasting research about the use of facilitated communication, an augmentative and alternative communication technique for teaching people with disabilities to communicate through pointing, or typing with support provided by a communication partner. We examine how researchers impose demands for the scientific validation of facilitated communication and use such demands to discredit autistic people identified with intellectual disabilities in their attempts to be recognized as knowers and producers of knowledge. Our analysis calls into question whether self-imposed limitations on contemporary knowledge production render educational research (in)capable of accepting forms of evidence that will facilitate the agency of those labelled or regarded as intellectually disabled and (in)capable of providing consumers of educational research access to knowledge that reflects the wide range of communicative, neurocognitive, and intellectual diversity in schools and communities.